Pemberdayaan Kelompok PKK Melalui Pelatihan Pembuatan Batik Jumputan Pewarna Alam sebagai Ciri Khas Desa Mojorejo Kabupaten Madiun - Cicilia Novi Primiani; Rafaella Chandraseta Megananda; Pujiati Pujiati (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The purpose of this community service is to empower the Family Welfare Empowerment (PKK) group by developing the creativity of natural dye batik products in order that they can become the typical batik of Mojorejo Village, Madiun Regency. The method of implementing the service activity is through the stages: 1) observation, 2) counseling, 3) training, and 4) evaluation. The target of service activity is the PKK group. The data collection technique used a questionnaire and an observation rubric. Descriptive data analysis is based on achievement indicators. Based on the questionnaire analysis, it was found that the creativity of the trainees increased by 40%. The motivation of the trainees increased by 70%. The understanding of the training participants about the process of making natural dyed batik increased by 90%. The conclusion of the service activity is that training on making Jumputan batik using natural dyes can increase the creativity of batik production, which is typical of Mojorejo Village, Madiun Regency.